2023
DOI: 10.1136/bjo-2022-322442
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of Graves’ orbitopathy within European Group On Graves’ Orbitopathy (EUGOGO) centres from 2012 to 2019 (PREGO III)

Abstract: BackgroundGraves’ orbitopathy (GO) is subject to epidemiological and care-related changes. Aim of the survey was to identify trends in presentation of GO to the European Group On Graves’ Orbitopathy (EUGOGO) tertiary referral centres and initial management over time.MethodsProspective observational multicentre study. All new referrals with diagnosis of GO within September–December 2019 were included. Clinical and demographic characteristics, referral timelines and initial therapeutic decisions were recorded. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
10
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 38 publications
6
10
0
2
Order By: Relevance
“…In our study the mean age was comparable to other reports (50.3y vs. 50.5y in PREGOIII) ( 35 ). However, the influence of age was less pronounced compared to previous reports.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our study the mean age was comparable to other reports (50.3y vs. 50.5y in PREGOIII) ( 35 ). However, the influence of age was less pronounced compared to previous reports.…”
Section: Discussionsupporting
confidence: 90%
“…In our retrospective analysis of a large single-center cohort female GO patients were much more common as in previous studies and similar to recent reports of tertial referral centers (PREGO III: 79.2% females vs. 82.2% here) ( 35 ). Our evaluation reaffirms the association of male sex with more severe stages of GO ( 18 , 20 25 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It has been shown that in GD lymphocytic Fig. 4 Histopathological images of mild and severe follicular hyperplasia obtained from GD patients and correlation to laboratory and thyroid volume at ultrasound. An example of mild and one of severe follicular hyperplasia of the thyroid are shown.…”
Section: Discussionmentioning
confidence: 99%